Bahan bakar padat dari biomassa bambu dengan proses torefaksi dan densifikasi - Azhar Azhar; Heri Rustamaji (Jurnal Rekayasa Proses, 2009)
Bamboo can be utililized as biomass through torrefaction and densification processes and be used as solid fuel. In the present work, bamboo was cut into pieces followed by torrefaction process in a furnace. The product of the torrefaction process was then milled or ground to produce smooth powder which was then pressed to form briquettes. The resulting briquettes were characterized by determining their calorific value, proximate analysis, ultimate analysis and burning rate. The torrefaction process was successfully carried out in a temperature range of 200-300°C to obtain charcoal that had following properties: brittle, hydrophobic with decreasing moisture content. The experimental results showed that the calorific value was influenced by bamboo briquette density. Greater the density higher the calorific value of the resulting brequettes. In addition, the rate of burning was also determined by the density. The briquettes that had higher density had lower burning rate. The results showed that torrefaction and densification processes could increase carbon content and calorific value of the bamboo brequttes by 19-20% in a temperature range of 200 – 300°C.